KONSTRUKSI MASYARAKAT RUSUNAWA SOMBO, SURABAYA TENTANG AKTIVITAS PENYALAHGUNAAN NARKOBA - Arifani, Nahdia (Paradigma, 2021)
Abstract This study discusses the construction of the Rusunawa Sombo community, Surabaya regarding drug abuse activities. The research is motivated by the large number of drug abuse activities that are "normal" seen and as if the local community agrees. The objectives of this study include 1) Identifying the objective conditions of the Sombo Rusunawa community 2) Identifying the values and norms that exist in the Sombo Rusunawa 3) Identifying the Sombo Rusunawa community understanding of drug abuse activities 4) Identifying the understanding and knowledge of the Sombo Rusunawa community about drugs and its consequences 5) Analyzing the construction of the Rusunawa Sombo community regarding drug abuse activities. The method used in thisresearch is qualitative with the perspective of Peter L. Berger’s social construction theory. The data analysis technique uses the Grounded theory technique. The social construction of the Rusunawa Sombo community, Surabaya regarding drug abuse activities occurs in three moments, namely internalization in the form of an understanding of "your business is not my business" socialized within the community. The moment of objectification is in the form of justification for the socialized understanding. Next is a moment of externalization in the form of a repetition of being normal, indifferent and silent when viewing drug abuse activities. Keywords: Social construction, drug abuse activity, society, indifferent